Perubahan Struktural dan Integrasi Harga Beras di Pulau Jawa - Nasution, Nazla Atikah Hikmatias; Akbar, Wahyu; Octariyadi, Nabila Umami; Andi, Laode; Sahara, Sahara (Ekonomis: Journal of Economics and Business, 2026)
The El Nino phenomenon and international trade policies have contributed to the fluctuations in Indonesian rice prices. Therefore, a comprehensive analysis of structural changes and price inequality in medium rice in Java Island during 2020-2024 is needed.To this end, daily price data from producer, wholesaler, and traditional market levels in 5 provinces were analyzed using the Houck approach, ECM, and cointegration test. Study findings show significant structural changes across Java Island capitals and provinces in February 2024, greatly affecting price stability analysis uncovers price discrepancy transmission differences. A response to price decreases outpaces that to price increases, suggesting bottlenecks in the supply chain. To stabilize prices and boost food security, the study suggests policies that support better distribution infrastructure and integration in the market.